Pedigree and genome-based patterns of homozygosity in the South African Ayrshire, Holstein, and Jersey breeds - Visser, Carina; Lashmar, Simon Frederick; Reding, Jason; Berry, Donagh P.; van Marle-Köster, Esté (Frontiers in Genetics, 2023)
The erosion of genetic diversity limits long-term genetic gain and impedes the sustainability of livestock production. This study aimed to perform a homozygosity-based evaluation of the South African Ayrshire (AYR), Holstein (HST), and Jersey (JER) dairy cattle breeds. Three sources of information, namely 1) single nucleotide polymorphism (SNP) genotypes (3,199 animals genotyped for 35,572 SNPs) 2) pedigree records (7,885 AYR; 28,391 HST; 18,755 JER), and 3) identified runs of homozygosity (ROH) segments were used to quantify inbreeding related parameters. The lowest pedigree completeness was for the HST reducing from a value of 0.990 to 0.186 for generation depths one to six. Across all breeds, 46.7% of the detected ROH were between 4 megabase pairs (Mb) and 8Mb in length. Two conserved homozygous haplotypes were identified in more than 70% of the JER population on Bos taurus autosome (BTA) 7. The JER breed displayed the highest level of inbreeding across all inbreeding coefficients. The mean (±standard deviation) pedigree-based inbreeding coefficient (FPED) ranged from 0.051 (±0.020) for AYR to 0.062 (±0.027) for JER, whereas SNP-based inbreeding coefficients (FSNP) ranged from 0.020 (HST) to 0.190 (JER) and ROH-based inbreeding coefficients, considering all ROH segment coverage (FROH), ranged from 0.053 (AYR) to 0.085 (JER). Within-breed spearman correlations between pedigree-based and genome-based estimates ranged from weak (AYR: 0.132 between FPED and FROH calculated for ROH <4Mb in size) to moderate (HST: 0.584 between FPED and FSNP). Correlations strengthened between FPED and FROH as the ROH length category considered lengthened, suggesting a dependency on breed-specific pedigree depth. The genomic homozygosity-based parameters studied proved useful in investigating the current inbreeding status of reference populations genotyped to implement genomic selection in the three most prominent South African dairy cattle breeds.